The muse - Dudycz Lupescu, Valya (Dudycz Lupescu, Valya. Mother Christmas, 2022)
It's the one story of magic and wonder everyone thinks they know--yet the most epic part of the tale remains shrouded in mystery. What actually happened 1,800 years ago to transform a starry-eyed young priest named Nicholas into a winter wizard destined to circle the world on a sleigh of hope? Now, the secret is revealed: She happened. This is the story of Amara, one of the legendary Muses of the House of Polyhymnia. Sent by the Muses to a small town in ancient Lycia, Amara sees something special in Nicholas's kindness and generosity. As she prepares to defend humankind against the Kobaloi, creatures who feed on fear and chaos, she senses this young man may be the partner she needs to stand against their growing power. But binding her fate and her magic to Saint Nicholas will mean breaking the laws of the Muses--and risking their eternal wrath.